Upcycled foods: A nudge toward nutrition - Thorsen, Margaret; Skeaff, Sheila; Goodman-Smith, Francesca; Thong, Brian; Bremer, Phil; Mirosa, Miranda (Frontiers in Nutrition, 2022)
One of the aims of the United Nations Sustainable Development Goals (SDG) is to end hunger and ensure access by all people to safe, nutritious, and sufficient food all year round. An obvious synergy exists between the second SDG ‘Zero Hunger’ and SDG target 12.3 which focuses on halving food waste and reducing food losses. In addition to helping improve global food security, reducing food waste provides financial and environmental benefits. Upcycling food is a technical solution for food waste reduction that retains the nutritional and financial value of food by-products. However, many of the upcycled foods produced are discretionary foods such as biscuits, crackers, and other snack food that are not part of a healthy dietary pattern, and should only be eaten sometimes in small amounts. Given the importance of ensuring a sustainable healthy diet, this paper discusses opportunities for upcycled food manufacturers to produce more nutritious products.